Protective effects of Bifidobacterium adolescentis on collagen-induced arthritis in rats depend on timing of administration. Issue 5 (8th May 2020) - Fan, Zhexin; Yang, Bo; Ross, R. Paul; Stanton, Catherine; Shi, Guoxun; Zhao, Jianxin; Zhang, Hao; Chen, Wei
Abstract : Early probiotics adminitration is a key timing to alleviate inflammation in rats with arthritis. Abstract : Emerging studies have addressed the role of probiotics in inflammation modulation via modifying gut microbiota. Perturbed gut microbiota is recognized as a pivotal trigger in the pathogenesis of rheumatoid arthritis (RA), and manipulating gut microbiota at the early phase may be helpful to alleviate the disease based on the fact that dysbiosis occurred prior to clinical arthritis. The current study compared the effects of preventive and therapeutic treatment with Bifidobacterium adolescentis on collagen induced arthritis (CIA) in rats. Early B. adolescentis administration before CIA modelling performed better than late B. adolescentis treatment in reducing the clinical symptoms, rebalancing the pro- and anti-inflammatory responses and maintaining the fecal concentration of short chain fatty acids (SCFAs), as well as restoring the intestinal dysbiosis. Preventive B. adolescentis treatment restored the gut microbiota to a normal level while late B. adolescentis fed rats showed clearly different gut microbial profiles. In addition, there were slight discrepancies between early- and late- treatment of B. adolescentis in the production of specific auto-antibodies and tight junction proteins. All those results highlighted that early treatment of probiotics in arthritis might be a better timing for alleviating arthritis.